The monitoring experience of a congenital heart disease patient with pulmonary artery stenosis and "sluggish skin" syndrome - Rakhima Mekenbayeva; Shuhrat Marassulov; Anar Sarsembayeva; Bahytzhan Nurkeyev; Rinat Maiorov; Daniyar Baigozhin; Nigina Mekenbayeva; Arman Akseitov (National Scientific Medical Center, 2019)
This article presents a clinical case of the follow-up of a patient with a congenital heart defect in the form of the pulmonary artery stenosis in the setting of the "sluggish skin" syndrome. It is shown that the occurrence of congenital defects largely depends on the hereditary factor, which, in this case, is a related marriage. You should also pay attention to the fact that the associated congenital heart disease: the mouth of the pulmonary artery against the background of the "sluggish skin" syndrome spontaneously stopped without surgery, which is probably due to the peculiarity of the background disease, that is, generalized elastolysis. The natural course of this congenital heart defect against the background of a genetic pathology in the form of "sluggish skin" syndrome indicates the positive influence of the pathological substrate (connective tissue hyperelasticity) on the state of the tissues of the heart and blood vessels. Despite the already available data, it is still difficult to make a prediction of the course of this disease. For a better understanding of the course of this pathological process, further observation of the patient is necessary.